TATA KELOLA SYARIAH DAN KINERJA KEUANGAN BANK SYARIAH DI INDONESIA: SHARIA GOVERNANCE AND FINANCIAL PERFORMANCE OF ISLAMIC BANKS IN INDONESIA - Paramitha, Tantri; Anugerah, Rita; Indrawati, Novita (Universitas Riau, 2025)
This study aims to analyze the impact of Sharia governance on the financial performance of Islamic commercial banks registered with the Financial Services Authority (OJK) during the 2021–2023 period. The background of this research lies in the high Non-Performing Financing (NPF) ratios observed in several Islamic banks, which indicate weaknesses in both financial performance and governance implementation. Sharia governance is measured using four variables: the Board of Directors, the Board of Commissioners, the Sharia Supervisory Board (DPS), and the effectiveness of internal audits. Financial performance is assessed using three indicators: Non-Performing Financing (NPF), Return on Assets (ROA), and Return on Equity (ROE). This study employs a quantitative approach using secondary data obtained from annual reports of Islamic banks, and the data analysis is conducted using SPSS software. The results show that all components of Sharia governance have a positive and significant effect on financial performance. This study contributes to a deeper understanding of the importance of effective Sharia governance in enhancing financial performance and building stakeholder trust in the Islamic banking sector.